Valuing the Invisible: A Sectorial Analysis of Intangible assets in India's Information Technology and Pharmaceutical Industries (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In the era of knowledge-driven economies, intangible assets have emerged as pivotal contributors to organizational value and competitive advantage. This research paper undertakes a comparative sectoral study of intangible assets in India’s Information Technology (IT) and Pharmaceutical sectors—two of the most innovation-intensive and globally competitive industries. The study explores the classification, strategic importance, and financial impact of intangible assets such as intellectual property, proprietary software, patents, R&D outputs, human capital, and brand equity. Through detailed case studies of leading Indian companies, this paper analyzes sector-specific approaches to asset creation, protection, and valuation. Furthermore, it evaluates legal frameworks, accounting standards (Ind AS 38, IFRS IAS 38), and policy implications associated with intangible asset reporting. The findings underscore the need for enhanced disclosure practices, regulatory reform, and strategic IP management. The paper concludes with actionable recommendations for stakeholders and outlines avenues for future interdisciplinary research. This study contributes to academic and industry discourse by offering insights into how intangible assets shape sustainable business models and national economic resilience.